Penyuluhan Pencegahan Penularan Penyakit dari Alat Selam (Mouthpiece) dan Tips Pemeliharan Kesehatan Gigi dan Mulut bagi Komunitas Penyelam "Corona Diving Club" - Dewi Priandini; Andy Wirahadikusumah; Johan Arief Budiman; Taufiq Ariwibowo (JURNAL ABDIMAS KESEHATAN TERPADU, 2023)
Diving Sports activities are very fun, because it is enjoyable. However, this sport is full of risks. If done carelessly, it will cause health problems including dental and oral health. The mouthpiece is the part that is attached to the SCUBA or snorkel equipment. In particular, the use of a mouthpiece has a negative impact on oral health, among other things, it can cause pain in the jaw (Temporomandibular Disorders), as well as transmission of diseases, name it bacteria, viruses or fungi. In 2020, the whole world, including Indonesia, was hit by a global pandemic in the form of Corona Virus Disease 19 (COVID-19) which has systematically changed human lifestyles. The Covid-19 pandemic is now gradually coming to an end. Therefore, it is necessary to carry out counseling and training regarding oral and dental health in the diver community during adaptation to new habits. Training and counseling will be carried out using online methods or distance learning using presentations on how to maintain dental and oral health in the Corona Diving Club diver community. Training and counseling were carried out for 20 community member cadres for 60 minutes, by giving presentations and followed by questions and answers. Increased knowledge about dental and oral health, measured by giving questionnaires before and after exposure to the material. The results are expected to increase the knowledge and abilities of the Indonesian cloth-loving community in Jakarta in maintaining oral health during the adaptation period to new habits during the Covid-19 pandemic. The outputs of this community service activity will be set forth in the form of HAKI PKM video recordings, leaflets and posters regarding dental and oral health care.